Silent son - Warfield, Gallatin (New York : Warner Books, 1995)
For prosecuting attorney Gardner Lawson a criminal case has come all too close to home. During a school outing, his eight-year-old son Granville by chance walked in on an armed robbery and double murder at a local grocery store. He is found unconscious, suffering from concussion, with the imprint of a gun barrel on his forehead. Ironically, Granville is the only person who can identify the killer - but when he wakes up he has no memory of the horrifying incident. As the search continues for the coldblooded murderer, it is increasingly obvious that Granville's memory must be restored - yet that might put him in physical as well as mental danger. Gardner is caught in a dilemma: he does not want to harm his son, yet he has to discover who committed the crime.
National College of Business and Arts
Keywords: Child witnesses -- Fiction; Detective and mystery fiction